Kajian Pendekatan Hermeneutika dalam Tafsir Al-Qur’an Perspektif Ulama Muslim Kontemporer - Mohammad Jailani; Nurkholis Nurkholis (Qur'an and Hadith Academic Society, 2021)
Hermeneutics of the Qur'an with its characters, namely Abu Zayd, Ali Harb, Arkoun, Hasan Hanafi, Syahrur, Khaled Abou el-Fadl, and Abdullah Saeed, has a hermeneutic method from the point of view of different theories and approaches. This paper aims to examine the study of the hermeneutics of the Qur'an from the perspective of contemporary scholars. The results of the study prove that the classical scholar's scholarship in the study of the Qur'anic science is different from the scientific method approach of contemporary scholars. This has implications for the civilizational culture of Tafsir Al-Qur'an. Therefore, this paper is very supportive to be used as a source of knowledge related to the study of the Qur'an.